2007
DOI: 10.1364/ol.32.001177
|View full text |Cite
|
Sign up to set email alerts
|

External cavity quantum cascade laser for quartz tuning fork photoacoustic spectroscopy of broad absorption features

Abstract: We demonstrate mid-infrared spectroscopy of large molecules with broad absorption features using a tunable external cavity quantum cascade laser. Absorption spectra for two different Freons are measured over the range 1130-1185 cm(-1) with 0.2 cm(-1) resolution via laser photoacoustic spectroscopy with quartz tuning forks as acoustic transducers. The measured spectra are in excellent agreement with published reference absorption spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…For all tuning mirror positions within this range, the measured ECQCL line width was smaller than the FTIR resolution of 0.5 cm -1 . Previous measurements have shown that the average line width of the ECQCL system is smaller than 0.2 cm -1 (Phillips et al 2007). While the instantaneous ECQCL line width is much smaller than 0.2 cm -1 , the average line width includes contributions from frequency chirp during the pulse and mode-hops on the external cavity modes, spaced by approximately 0.04 cm -1 .…”
Section: Figure 2 Photograph Of Ecqcl Systemmentioning
confidence: 89%
“…For all tuning mirror positions within this range, the measured ECQCL line width was smaller than the FTIR resolution of 0.5 cm -1 . Previous measurements have shown that the average line width of the ECQCL system is smaller than 0.2 cm -1 (Phillips et al 2007). While the instantaneous ECQCL line width is much smaller than 0.2 cm -1 , the average line width includes contributions from frequency chirp during the pulse and mode-hops on the external cavity modes, spaced by approximately 0.04 cm -1 .…”
Section: Figure 2 Photograph Of Ecqcl Systemmentioning
confidence: 89%
“…While QEPAS sensors generally operate in a narrow spectral window around the sharp absorption peak of a given small-mass molecule [4][5][6][7][8][9][10][11], our sensor uses a widely tunable laser source to scan a vast portion of the spectrum, to detect and recognize the fingerprints of a number of relatively complex molecules with broad absorption patterns. A few examples of this approach are reported in the literature [12][13][14][15]. Also our QEPAS cell implements heating elements and microfluidic connections with minimized dead volumes, which make the sensor arranged for hyphenation with sampling, preconcentration, and micro-Gas Chromatographic separation modules.…”
Section: Introductionmentioning
confidence: 99%
“…The transduction displacement has been studied using the photo acoustic spectroscopy [4]. Laser photo acoustic spectroscopy has been used for trace detection of vapors, gas and aerosols [5][6][7][8]. Photo acoustic spectroscopy has also been utilized for detection of explosives and other remote sensing applications [9,10].…”
Section: Introductionmentioning
confidence: 99%